Survey on Monitoring Aquatic Debris Using Smartphone-Based Robots (International Journal of Engineering and Computer Science, 2017)
Marine debris is an important environmental issue. It provides threats to our ecosystems, water transport and life of living things in both land and water. So monitoring aquatic debris is very important to the entire world. Numerous techniques are implemented for monitoring aquatic debris. The ultimate goal of this paper is to discuss existing methods for observing debris in aquatic environment.